Diasporic Consciousness in Kiran Desai’s The Inheritance of Loss - Shrestha, Ravi Kumar (Patan Pragya, 2023)
The Inheritance of Loss written by Kiran Desai is a South Asian Novel written in English reflects the diasporic consciousness of the characters since the characters have feelings of a sense of loss, hybrid identity, consciousness of being an outsider, longing for home, double consciousness, split personality, and alienation. Regarding diasporic consciousness, human beings have had such consciousness since they started migrating to other nations leaving their nations due to their compulsion to adapt in the culture of the host land along with the culture of the root land. However, this research focuses on the diasporic consciousness of protagonists such as Biju, Jemu Bhai Patel, Fathe Booty and Sai potrayed in The Inheritance of Loss in the post-colonial era. The research discovers the impact of post-colonialism on these characters, which means that India became independent in 2047, but Indians throughout the world are still under the influence of colonialism. Biju’s life in New York, Jemu Bhai Patel’s life in London and Sai’s life in Kalimpong reveal their sense of loss, dislocation, split personality, double consciousness and hybrid identity, which reflect their consciousness in diaspora. Hence, for the research methodology, the qualitative approach is applied since the research deals with the fictional characters portrayed in the select novel. Likewise, for the broad theoretical framework, Avtar Brah’s and Vijay Mishra’s theory of diaspora, and Homi K. Bhabha’s Hybrid Identity are applied as theoretical tools to explore how the characters struggle for identity, suffer due to loss of identity and are under the influence of colonialism in the diaspora.